1996
DOI: 10.1159/000169014
|View full text |Cite
|
Sign up to set email alerts
|

Early and Late Effects of Erythropoietin on Glucose Metabolism in Maintenance Hemodialysis Patients

Abstract: The effects of recombinant human erythropoietin (rHuEPO) on the glucose metabolism were evaluated by intravenous glucose tolerance test in 20 maintenance hemodialysis patients. In 8 cases the glucose tolerance tests were performed before and after a single intravenous injection of 50 IU/kg of rHuEPO and in 12 cases before and after 3 months of rHuEPO therapy at doses of 50 IU/kg three times/week and 2 weeks after rHuEPO withdrawal. For each test glucose, immunoreactive insulin (IRI), and C peptide (C-p) plasma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 15 publications
0
25
0
Order By: Relevance
“…abnormalities and increased insulin sensitivity, with the duration of the treatment positively correlating with insulin sensitivity in these patients (188)(189)(190).…”
Section: Epo In Treatment Of Cardiovascular Diseasesmentioning
confidence: 81%
“…abnormalities and increased insulin sensitivity, with the duration of the treatment positively correlating with insulin sensitivity in these patients (188)(189)(190).…”
Section: Epo In Treatment Of Cardiovascular Diseasesmentioning
confidence: 81%
“…Borissova et al [9]have observed an improvement of peripheral insulin sensitivity in 5 diabetic patients on haemodialysis, after rHuEPO treatment, which was attributed to improvement of tissue oxygenation due to increased Hct. Allegra et al [10]noticed an improvement of the glucose metabolism after long-term rHuEPO therapy, not related to a direct effect or correction of anaemia according to their findings, while after short-term administration they did not find any effect. In the present study, no patient had haemosiderosis, and all of them improved their tissue insulin sensitivity before any correction of anaemia, as a response to EPO treatment.…”
Section: Discussionmentioning
confidence: 93%
“…The possible role of the eventual correction of malnutrition was also suggested. 5 In a recent study, insulin resistance improved signi¢cantly 10 days after the beginning of EPO treatment, before the rise of haematocrit. There was no further improvement of insulin resistance after the correction of haematocrit level, at least 8 weeks later.…”
Section: Discussionmentioning
confidence: 95%
“…EPO therapy significantly improves glucose metabolism in maintenance HD patients mainly by reduction of insulin resistance. 5 Since neither anaemia correction nor a direct e¡ect of rHuEPO on some metabolic steps seem to be responsible for these e¡ects, further studies are needed on EPO treatment for improvement of insulin resistance in HD patients. Although both EPO and pulse oral 1-a-D3 treatments corrected anaemia of these patients signi¢-cantly, only EPO produced a marked decrease in lymphocyte PC-1 activity.…”
Section: Discussionmentioning
confidence: 99%